Development of a high performance routing protocol for wireless ad hoc networks - Rethinavelu, Senthil. (2013)
In a wireless ad-hoc network where wireless links are established by connecting to different devices like laptops and mobile phones, it is difficult to maintain the link as the devices (nodes) are constantly moving around. Therefore, in order to improve the efficiency of a transmission link so as to increase the throughput, different algorithms or methods have been implemented. One such algorithm is the Location-Aided Routing (LAR) protocol in which all the nodes are flooded with the Route Request (RREQ) packets until the packets reach the destination node. Despite the workability of this protocol, the throughput was not high. In an effort to improve the efficiency, this project was proposed.